Simulating neutral hydrogen across cosmic time: the 21-cm forest in late reionization models and the global 21-cm signal at cosmic dawn - Tomáš, Šoltinský (2023)
The 21-cm line has a potential to be a powerful probe of the intergalactic medium (IGM) during the Cosmic Dawn and the Epoch of Reionization. Various observatories such as LOFAR and SKA aim to observe this line. To aid these observational efforts, I use cosmological simulations drawn from the Sherwood-Relics programme in which a novel hybrid approach of coupling hydrodynamical simulations with radiative transfer is implemented to model the 21-cm forest during the Epoch of Reionization and sky-averaged 21-cm signal during Cosmic Dawn.